Responses of soil available nutrients and microbial performance in a newly established apple orchard after five-year fertilization with different sources of livestock manure - Ying Liu; Meng Xu; Mengjiao Liu; Cungang Cheng; Long Qiao; Yanqing Li; Zhuang Li (Journal of Agriculture and Food Research)
Apple is a widely cultivated fruit in the world, and China is the country with the largest apple planting area and production. It is of great agricultural and economic significance to study the fertilization strategy of new apple orchards on poor soil. Under the same nitrogen input, the effects of different livestock manure (chicken manure, swine manure, sheep manure, and cattle manure) and chemical fertilizers were compared in fertilized and non-fertilized area after five-years continuous fertilization. The results showed that compared with the fertilizer applied area, soil available nutrients were lower in the non-applied area. In fertilizer applied area, the soil NO3−-N content was significantly increased by manure application, except chicken manure, when compared with chemical fertilizer. However, the available P and K contents under the chicken manure application were significantly higher than those in all other treatments, except for the available P content under the swine manure application. All manure treatments increased the alpha diversity of microorganisms and the dominant populations of microbial species at the phylum level were consistent. Redundancy and correlation analyses showed a significant positive correlation between Actinobacteria, Chloroflexi, and available P and a significant negative correlation between Glomeromycota and available P. A significant negative correlation was observed between Firmicutes, Planctomycetes, and available K. The highest Chao1 and Shannon indices were achieved under the swine manure application. The microbial community structure under the chicken manure treatment was different from that under the other manure treatments. The study initially identified differences in the performance of fertilizers from different sources, and found that swine and chicken manures have significant effects on improving soil fertility and microbial diversity, which provided scientific basis for soil management and fertilizer selection in practical agricultural production.